A interrupção da informalidade no campo da cachaça de alambique: uma análise sob a ótica do trabalho institucional de participantes de uma associação - Morais, Raphael de (2019)
Informality appears as one of the negative factors in the field of alembic cachaça, contributing to damage its image as a beverage that has historicity and cultural tradition in Brazil. It is estimated that 85% of alembic cachaça producers act in the informal sector only in the state of Minas Gerais, which ends up affecting the whole productive chain, and even consumers who can consume a drink that has a poor quality, different from the stills operate within the formality. Several efforts have been made in recent times to improve the image of alembic cachaça in Minas Gerais and Brazil, and ANPAQ, the National Association of Producers and Members of the Cachaça Production Chain, is responsible for this change in image. The oldest representative of the sector in Brazil, develops several works in the sense of promotion, valorization and defense of alembic cachaça. Because of the foregoing, which has been included under one of the currents of the Institutional Theory and understanding that informality is a strong institution endowed with symbolism and historicity, the objective of this work is to understand the institutional work carried out by managers of the association of cachaça producers (ANPAQ). The contributions of this work to the interruption of informality and legitimacy of this organization. The theoretical current that bases this work is recent and denominated Institutional Work, which offers three analytical pillars: creation, perpetuation or interruption of institutions, being the last pillar chosen to carry out the analyses of this study. The present research is a case study, qualitative and descriptive. In-depth interviews with managers and associates were used as data collection tools, as well as documentary analyzes in institutional archives and booklets supported by the association with a focus on the regulation of informal stills. Thematic content analysis was performed as an analytical method in order to construct the presented results. The main points made are that some historical factors such as high taxation, the stigma of origin and consumption, besides the high bureaucratic requirements are those responsible for fomenting informality as an institution in the field of alembic cachaça. In turn, informality can be configured in three different ways, namely: the producers' lack of knowledge about the demands; by the financial impossibility or as evasion of production, from the formal ones. To address these problems, the association develops an institutional work around the valorization of cachaça through the seal of quality, courses, and events. In addition to these actions, ANPAQ also occupies spaces and conducts government partnerships to improve tax issues and attempts to change legislation for a possible reduction of bureaucracy for alembic cachaça, in order to make formalization more accessible. Add to these works the association's struggle to remain active in the alembic cachaça field, which has not been much perceived by associates who are more distant from the association, representing a difficulty that still has to be solved by it a real strengthening.